Role of Ficus carica in Alleviating Chronic Hypoxia Impact in Rat’s Lungs - Anggraini, Dini; Meliala, Andreanyta; Siswanto; Fitria, Laksmindra; Narwidina, Paramita; Mahroos, Rifda El; Sudesty, Shellya Puti (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Chronic Intermittent Hypoxia (CIH) can initiate oxidative stress and inflammation. Ficus carica is known to contain antioxidant compounds capable of suppressing oxidative stress. This study aims to investigate the protective role of Ficus carica puree (FCP) on the levels of Malondialdehyde (MDA), Superoxide Dismutase (SOD), SOD/MDA ratio, Platelet Lymphocyte Ratio (PLR), and Tumor Necrosis Factor-α (TNF-α) in the lungs of rats induced by CIH. Rats were treated with FCP at doses of 1.25 ml/200g (CIH-F1), 2.5 ml/200g (CIH-F2), and 5 ml/200g (CIH-F3). All rats, except for the neutral control group, were subjected to chronic intermittent hypoxia (CIH) for 4 hours/day for 30 days. The CIH-F2 and CIH-F3 groups demonstrated significantly lower levels of lung MDA compared to the CIH group. The CIH-F3 group showed a considerably lower level of lung SOD compared to the CIH group. However, the SOD/MDA exhibited a considerably greater value in the CIH-F3 induction group compared to the other groups. The TNF-α in lungs and PLR levels were significantly lower in the CIH-F3 group than in the CIH group. These findings suggest that FCP may serve as a functional food to mitigate the negative impact of hypoxic circumstances on lung health.